2010
DOI: 10.2353/ajpath.2010.090865
|View full text |Cite
|
Sign up to set email alerts
|

Synoviocyte-Derived Angiopoietin-Like Protein 2 Contributes to Synovial Chronic Inflammation in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by symmetrical polyarticular synovitis of the diarthrodial joints. Several proinflammatory cytokines derived from both infiltrating inflammatory cells and activated resident cells within the RA joint play a fundamental role in the processes that cause inflammation. However, anticytokine treatment is beneficial but not curative, the effects are only partial, and nonresponses are common. Therefore, an effort has been made to identify other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 52 publications
1
92
0
Order By: Relevance
“…Since then, epidemiologic studies have confirmed the idea that chronic inflammation underlies many cancers (2). Recently, we reported that Angiopoietin-like protein 2 (Angptl2) acts as a chronic inflammatory mediator in several pathologic settings (3)(4)(5)(6), and demonstrated that increased Angptl2 expression in skin tissues promotes inflammation and accelerates carcinogenesis in a chemically induced squamous cell carcinoma (SCC) of the skin mouse model by increasing susceptibility to "preneoplastic change" and "malignant conversion" (7). In normal cells, initiating oncogenic mutation is considered essential to promote a "preneoplastic change," which, if unrepaired, is then followed by proliferation and acquisition of cellular survival capacity, allowing accumulation of additional mutations (8)(9)(10).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Since then, epidemiologic studies have confirmed the idea that chronic inflammation underlies many cancers (2). Recently, we reported that Angiopoietin-like protein 2 (Angptl2) acts as a chronic inflammatory mediator in several pathologic settings (3)(4)(5)(6), and demonstrated that increased Angptl2 expression in skin tissues promotes inflammation and accelerates carcinogenesis in a chemically induced squamous cell carcinoma (SCC) of the skin mouse model by increasing susceptibility to "preneoplastic change" and "malignant conversion" (7). In normal cells, initiating oncogenic mutation is considered essential to promote a "preneoplastic change," which, if unrepaired, is then followed by proliferation and acquisition of cellular survival capacity, allowing accumulation of additional mutations (8)(9)(10).…”
Section: Introductionmentioning
confidence: 81%
“…Our previous report showing chronic inflammation in skin tissue of K14-Angptl2 Tg mice demonstrated infiltration of skin tissue by inflammatory cells, including activated macrophages and neutrophils (7), both of which are sources of ROS (36). Angptl2 reportedly activates NFkB proinflammatory signaling in various cell types (3)(4)(5)(6)(7)37), which also enhances ROS production (38). Taken together, Angptl2 secreted from skin tissue of K14-Angptl2 Tg mice may increase ROS production due to activity of infiltrated and activated inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reported that 9 months of CAT magnified 50-folds the rise in COX2 expression associated with aging in the mouse aorta [26]. Angptl2, on the other hand, is associated with inflammation as its presence is increased in patients with rheumatoid arthritis and abdominal aortic aneurysm [47,69], while its deletion can lower pro-inflammatory cytokines in rodents [67,69]. Hence, our results suggest that early CAT treatment induces a pro-inflammatory environment upon the challenge of a WD: we propose that CAT limited the development of antioxidant defense mechanisms able to counteract the stress induced by the WD.…”
Section: Inflammationmentioning
confidence: 93%
“…Quantitation of ANGPTL2 protein by ELISA ANGPTL2 concentrations in tissue lysates or in culture medium from tumor cells were estimated by an ANGPTL2 Assay Kit (IBL), as described (12,13). For tissue lysates, proteins were extracted from 2 mg of tumor or nontumor tissue and dissolved in 10 mL lysis buffer [300 mmol/L NaCl, 50 mmol/L Tris-HCl (pH 7.5), 1% Triton X-100, and 1mmol/L EDTA].…”
Section: Methodsmentioning
confidence: 99%